Calcium Dependent Reversible Aggregation of Escherichia coli Biomimicking Vesicles Enables Formation of Supported Vesicle Layers on Silicon Dioxide - Duša, Filip; Chen, Wen; Witos, Joanna; Wiedmer, Susanne K. (Frontiers in Materials, 2019)
The importance of using biomimicking membranes for various biological applications is rising, as such models are relevant for imitating real organisms. In addition, biomimicking membranes are usually much more repeatable in preparation and easier to handle during analysis than real organisms or biological membranes. In this work we developed a method for the adsorption of intact small unilamellar Escherichia coli (E. coli) vesicles (size Z-average of 73 nm) on SiO2 substrate material. We describe the adsorption process based on the use of two surface sensitive techniques, i.e., nanoplasmonic sensing (NPS) and quartz crystal microbalance (QCM). The acquired data show that the adsorption follows a two-step process. The first step is a slow adsorption of E. coli vesicle aggregates held together by 5 mM of calcium (size Z-average of 531 nm). The Z-average of the aggregates decreased almost three times when the calcium concentration was decreased to 0.1 mM. This suggests that the aggregates were disassembling to some extent when calcium was removed from the system. With both techniques, i.e., NPS and QCM, we observed a second rapid adsorption step after the solution was changed to deionized water. In this second step, the aggregates started to fall apart as the calcium concentration dropped, and the released vesicles started to adsorb onto unoccupied spots at the SiO2 surface of the sensors. Extensive release of mass from the surface was confirmed by QCM, where it was reflected by a sharp increase of frequency, while NPS, due to its lower sensing depth of a few tens of nanometers, did not record such a change. Taken together, we have developed a protocol to form a supported vesicle layer of E. coli vesicles on SiO2 surface using sodium 4-(2-hydroxyethyl)piperazine-1-ethanesulfonate buffer, thus enabling the preparation of E. coli biomimicking supported vesicle layers for interaction studies of compounds of interest. The immobilization happens via a two-step adsorption process.